Faktor-Faktor yang Memengaruhi Komplikasi Persalinan Wanita Usia Subur di Indonesia Menggunakan Data SDKI 2012 (Aplikasi Analisis Regresi Logistik Biner Multilevel) - Fakhri Aliyudin; Budyanra - (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2016)
Maternal Mortality Rate (MMR) is still a crucial problem in Indonesia considering the incidence rate is still high enough that is about 359 per 100,000 births. The biggest cause of MMR in Indonesia is due to the high incidence of birth complications. This papers aims to determine the factors that affect the incidence of birth complications in women of childbearing age in Indonesia by using regression of logistic biner multilevel analysis. The data used are sourced from Indonesia Demographic and Health Survey 2012 (SDKI-2012). Based on the results of data processing, it is known that variables of parity, pregnancy complications, history of previous complications and ratio of health centers per 100,000 population are significantly affect the incidence of birth complications in women of childbearing age in Indonesia